Analisis dan Perancangan Sistem Informasi Pengelolaan Retain Sample QC pada PT. XYZ - Fajriyah, Nurul; Setiawan, Wawan (Jurnal Teknologi Terpadu, 2022)
Along with the development of science and technology, it has become an essential requirement in companies to produce information quickly, precisely, and accurately. PT. XYZ is a company engaged in the food processing industry. In each production process, strict quality control is required to produce the best quality. The current retain sample management system still uses manual and non-computerized records, including preparing Physico-chemical test analysis reports and incoming and outgoing transactions for retained samples made by the QC Leader. This study uses data collection methods through observation, interviews, and literature. The proposed system development uses the waterfall method to design the system using UML (unified modeling language), programming using visual basic 6.0, and Microsoft Access 2007 database. The results of the research that has been done, namely the creation of an information system for managing QC retain samples at PT. XYZ. The system design uses use case diagrams to describe the system user actors, activity diagrams to describe the system's process, sequence diagrams to describe the data flow interface to the database, and class diagrams to describe the relationships between tables. Then the system design is implemented in Visual Basic 6.0 programming language and MS database Microsoft Access. All data is integrated into one database so that the required data and reports can be presented computerized, such as physicochemical test analysis data, incoming and outgoing sample transactions, and samples that have entered their expiration period.